Pengaruh Work Family Conflict Terhadap Komitmen Organisasi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
Human resources are an important component in a company. The progress of the companycan be seen from the involvement of human resources in it. The purpose of this study is todetermine the effect of Work Family Conflict on organizational commitment. The researchmethod uses a descriptive verification approach with quantitative data types. The studypopulation was employees of PT. Shoetown Majalengka, totaling 323 employees. The samplewas determined using random sampling techniques with a sample size of 100 employees, witha Likert scale of measurement (1-5). Data analysis was performed through correlationanalysis, and t-test with processing using the SPSS Version 21 application. The resultsshowed that Work Family Conflict had a negative and significant effect on organizationalcommitment